2010
DOI: 10.2190/pm.40.4.h
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Meditation on Psychological Distress among Buddhist Monks and Nuns

Abstract: This study shows that Monks and Nuns who are more advanced in practicing meditation show fewer signs of psychological distress than Monks and Nuns who are less advanced in the art of meditation. The practice of meditation may have therapeutic value in the management of psychological distress, and could be offered as a non-pharmacological treatment alternative in patients with anxiety and depression. This is a preliminary study with limitations. More robust evidence is needed before we can confidently establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Neither was there a signi cant difference between the monks and nuns (U = 3185, p = 0.20). Using diagnostic criteria from previous reports, 244 (58.3%) monastics were in the minimal severity range (0-4), 119 (31.0%) in the mild severity range (5-9), 34 (8.90%) in the moderate severity range (10)(11)(12)(13)(14), 6 (1.60%) in the moderately severe range (15)(16)(17)(18)(19), and 1 (0.30%) in the severe range (20)(21)(22)(23)(24)(25)(26)(27) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither was there a signi cant difference between the monks and nuns (U = 3185, p = 0.20). Using diagnostic criteria from previous reports, 244 (58.3%) monastics were in the minimal severity range (0-4), 119 (31.0%) in the mild severity range (5-9), 34 (8.90%) in the moderate severity range (10)(11)(12)(13)(14), 6 (1.60%) in the moderately severe range (15)(16)(17)(18)(19), and 1 (0.30%) in the severe range (20)(21)(22)(23)(24)(25)(26)(27) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Monastics often primarily consume a vegetarian diet, which has been associated with a reduced prevalence of depression (14). Moreover, some -though not all -Tibetan Buddhist monastics maintain regular contemplative practices, which have positive effects on mental health and well-being (15). In addition to practices, Buddhist belief systems may buffer monastics from the harmful effects of stress or trauma, and may provide a mental framework that shapes symptoms of depression and mental distress (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, one study examined meditation and mental health in the Indian monastics, 18 and another examined Zen training and mental health and quality of life in Japanese monk trainees. 17 However, it was uncertain if the type of meditation involved mindfulness meditation.…”
Section: Mental Component Summarymentioning
confidence: 99%
“…In contrast, a recent systematic review and meta-analysis found in favour of yoga when compared to aerobic exercise or usual care (including group therapy, support group, or pharmaceutical intervention, but also wait-list control) [47]. While some studies suggest a cumulative psychological advantage in long-term meditators [64, 65] and lower rate of depression remission at 9-month follow-up for group yoga [66], overall, there is a paucity of longitudinal follow-up studies investigating the long-term effects of yoga.…”
Section: Yoga To Treat Depressionmentioning
confidence: 99%